Application of ABC VEN Method in Procurement Management and Its Impact on Internal Business Processes that Impact General Patient Customer Retention in 2022 (Case study at RS X) - Juminar, St Ratna; Saragi, Sahat; Andayani, Nurita (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT X Hospital wants to increase the efficiency of pharmaceutical services by replacing the consumption-based drug procurement method with the ABC VEN method to overcome challenges such as out-of-stock, direct purchases from other vendors, and the use of multiple vendors, with a potentially positive impact on customer retention and compliance with relevant regulations and research. This study aims to examine the application of the ABC VEN method to improve inventory procurement planning at X Hospital, compare its effectiveness with the consumption method on internal business processes, and measure its impact on customer retention. This study uses a non-experimental approach with quantitative descriptive and observational retrospective, analyzes drug procurement January-July 2022, and evaluates the ABC VEN method from December 2022 through informant interviews at X Hospital to analyze internal business processes and retention of customers using the Balanced Scorecard approach. The number of samples used was 175 samples. The analysis of validation and reliability tests showed that most of the indicators on the satisfaction aspect were in the high category, while overall patient satisfaction was in the sufficient category. The indicators on the assurance and tangible dimensions are included in the sufficient category, showing attention to the availability of drugs and seating facilities to increase customer retention. The application of the ABC VEN Method at X Hospital from August to December 2022 has a higher realization rate (87%) than the Consumption Method (66%), with a direct procurement efficiency of 57% or IDR 64,816,401. Despite payment constraints, related parties consider implementing the ABC VEN Method more effective and can improve internal business performance and customer retention. Keywords: X Hospital, ABC VEN Method, Pharmacy Services